Identification of esophageal and stomach cancer risk factors among the population of Kazakhstan with the use of QCancer e-base calculator - Galiya Orazova; Leonid Karp; Gulnar Rakhimbekova; Anargul Nogayeva (National Scientific Medical Center, 2016)
Objective: Identify esophageal and stomach cancer risk factors among urban and rural population of Kazakhstan with the use of QCancer e-base calculator. Methods. This work is a descriptive, cross-sectional, multisample, noninvasive study. In 2013-2014 we hold an opinion poll among Kazakhstan population jointly with the primary healthcare professionals in order to identify the primary symptoms and risk factors of esophageal and stomach cancer. Target of the research was the population (general population), i.e. persons, which are not registered with esophageal and stomach cancer (1112 respondents), as well as patients, which are under examination and treatment in oncological dispensaries with this oncopathology (403 respondents). For creation of the population profile we selected respondents at the age of 40-59 years. Results. As of today, the most "affecting" risk factors of esophageal and stomach cancer among the population of Kazakhstan are nutrition disorders, then social habits and hereditary background. Distribution of the studied cohorts according to the risk degree allowed to identify the following regularities: proportion of persons with a high risk degree is considerably larger among males, than among females (р<0,05); proportion of persons with a high risk degree among persons in the 50-59 years old group is larger, than in the same group of 40-49 years old (р<0,05); among males, the proportion of persons with a high risk among urban and rural population is approximately similar. At the same time, share of rural females with a high risk degree considerably exceeds the share of urban females with a high risk. Conclusion. Formation of persons group with the cancer development risk with the help of QCancer calculator allows to optimize further measures for prevention and early detection of esophageal and stomach cancer.